Ta szkoła symbolicznie rozstrzelała się sama… Filmy Słoń, Carrie, Nad krawędzią w dyskusji o problemach współczesnej szkoły i młodzieży podczas zajęć z pedagogiki na specjalnościach nauczycielskich - Jaskulska, Sylwia (Kultura-Społeczeństwo-Edukacja, 2016)
In the paper, apart from interpreting the message of films: Carrie (directed by Brian De Palma), Over the Edge (directed by Jonathan Kaplan) and Elephant (directed by Gus Van Sant), I also describe how classes can be arranged around them. Thus, I join the debate on the space for such productions in education, especially in the methodology for training teachers-to-be. I indicate possible applications of feature films and a wide spectrum of benefits that follow from this approach. In fact, movies are still an undervalued but very effective didactic tool that engages pupils in authentic intellectual tasks that deal with important content and issues.